Pengaruh Debt Toequity Ratio (Der), Net Profit Margin Ratio (NPM), Dan Return on Equity Ratio (ROE) terhadap Harga Saham Industri Pertambangan yang Terdaftar pada LQ45 di Bursa Efek Indonesia (BEI) Periode 2013 – 2017 - Eka Desi Pratiwi; Atikah Atikah; Masnun Masnun (Universitas Batanghari Jambi, 2020)
The purpose of this study is as follows : 1. To analyze the effect of Debt To Equity Ratio (DER), Net Profit Margin Ratio (NPM) and Return On Equity Ratio (ROE) simultaneously on the mining industry stock price listed on LQ45 in Indonesia Stock Exchange (IDX) period 2013-2017, 2. To analyze the effect of Debt To Equity Ratio (DER), Net Profit Margin Ratio (NPM) and Return On Equity Ratio (ROE) partially against the stock price of mining industry listed on LQ45 in Indonesia Stock Exchange (IDX) period 2013-2017. The type of data required and collected in this study is quantitative data. Quantitative Data in the form of company's financial statements in mining industry companies. The data source used in this study is to use secondary data. In this study the authors took an object in the form of companies of the mining industry. The mining industry company is one of the companies assumed to be able to produce optimal profit. This makes the authors interested in making the mining industry an example of this study Based on the results of multiple regression analyses that the regression equation Y= 1,305- 2.307 X1t- 0,890 X2t+ 0,084X3t + e. The influence of Debt To Equity Ratio (DER), Net Profit Margin Ratio (NPM) and Return On Equity Ratio (ROE) to stock price is 12% while The remaining 88% is influenced by other factors outside of this study. Simultaneously the Debt To Equity Ratio (DER), Net Profit Margin Ratio (NPM) and Return On Equity Ratio (ROE) affect the share price of mining industry company on LQ45 listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017. There are partially the influence of Debt To Equity Ratio (DER), Net Profit Margin Ratio (NPM) and Return On Equity Ratio (ROE) to the stock price of mining industry company on LQ45 listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017